Perwujudan Tindak Kesantunan Pragmatik Tuturan Imperatif Guru Dalam Proses Pembelajaran Bahasa Indonesia Di Kelas XI SMK Negeri 8 Surakarta - Romadloni, Nurul Tri, Drs. Andi Haris Prabawa, M.Hum (2016)
This study has two objectives to 1) describe the types of meaning pragmatics of speech imperative that teachers use in learning interaction Indonesian in class XI SMK Negeri 8 Surakarta. 2) To describe the politeness pragmatic speech imperatives of teachers who are in the learning interaction Indonesian in class XI SMK Negeri 8 Surakarta. The subject of this research that Indonesian teachers and students of class XI in SMK Negeri 8 Surakarta. Object of research is imperative utterances that occur during the learning process in class XI Indonesian Negeri 8 Surakarta. The data in this study is a narrative imperative form of the word, or phrase in the communication between teachers and students containing speech imperative during the learning process in the classroom. The source of the data Indonesian learning interaction in class XI SMK 8. Data collection techniques used in the study were recording technique and technique refer to note. This study uses two kinds of triangulation, the first triangulation techniques or methods of collecting data and the second data method. Data analysis techniques used in this research is the method frontier. The results of this study can be concluded that: 1) type - the type of meaning pragmatics of speech imperative that teachers use in learning interaction Indonesian in class XI SMK Negeri 8 Surakarta, covering speech which implies a pragmatic imperative messengers, speech which implies a pragmatic imperative demand, speech which implies a pragmatic imperative persilaan, speech which implies a pragmatic imperative invitation, which implies a pragmatic speech imperatives permit, and the utterances which implies pragmatikimperatif ban. 2) Politeness Imperative speech contained in the teacher Indonesian learning interaction in class XI SMK Negeri 8 Surakarta.Hasil study found some politeness narrative prose Indonesian language learning in SMK Negeri 8 Surakarta five types: declarative construction, imperatives, and interrogative constructions construction ekslamasive. Keywords: Politeness, Imperative speech, learning Indonesia